The Finite Element Method : Its Basis and Fundamentals - Zienkiewicz, O. C. (Olgierd Cecil), author 226191; Taylor, R. L., author 464501; Zhu, J. Z., author 189721 (Oxford : Butterworth-Heinemann, 2013)
The Finite Element Method: Its Basis and Fundamentals offers a complete introduction to the basis of the finite element method, covering fundamental theory and worked examples in the detail required for readers to apply the knowledge to their own engineering problems and understand more advanced applications.